Attitude to weapons and military culture of the Adyghe population in the Republic of Adygea - Murat Yu. Donezhuk (Кавказология, 2024)
The article examines how modern Circassians living in the Republic of Adygea relate to the issues of carrying weapons, serving in the army, as well as elements of traditional military culture. The results acquired from two ethnosociological studies suggest that modern Circassians have nearly the same attitude toward weapons as the people of the Russian Federation as a whole, i.e. they mostly oppose the licensing of particular types of military weapons. It is also clear that, for respondents, traditional military culture has lost its relevance. The respondents believe that a man is a warrior, this is rather a spiritual state, while in traditional culture it was believed that this is a certain complex in which weapons play the crucial role. A whole range of reasons influenced such changes, including the standardization of the youth education system, a targeted disarmament policy, and the establishment of relative calm in the region at the end of the 19th century.